Transition, violence and social movement: conceptualization and visibility of the domestic violence in Uruguay 1984-1995 - Martínez Hernández, Lucía Verónica (Revista de Historia Social y de las Mentalidades, 2019)
This paper analyzes the transformations of the interpretative framework with respect to violence, within the Women and Feminist Movement of Uruguay between 1984 and 1995. The research seeks to account for the process of construction of the category of domestic violence and its relationship with the disputes of sense about democracy, through the analysis of the press of the time -particularly the feminist press-. The results confirm that the conceptualization, visibility and concretion of the first tools for dealing with domestic violence are the result of a sustained work of the Women and Feminist Movement of Uruguay.
Keywords: Transition; Domestic Violence; Women and Feminist Movement; Uruguay